2022
DOI: 10.3389/fphar.2022.979634
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer potential of cryptotanshinone on breast cancer treatment; A narrative review

Abstract: Breast cancer has recently been known as the first lethal malignancy in women worldwide. Despite the existing treatments that have improved the patients’ prognosis, some types of breast cancer are serious challenges to treat. Therefore, efforts are underway to provide more efficient therapy. Cryptotanshinone (CPT) is a liposoluble diterpenoid derivation of a traditional Chinese herbal medicine called Salvia miltiorrhiza Bunge. It has been considered in the past decades due to its vast therapeutic properties, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Cryptotanshinone (CTN) is a diterpenoid monomer and a lipophilic component extracted from the dried roots and rhizomes of the traditional Chinese herb S. miltiorrhiza ( Li et al, 2021 ; Zhang et al, 2023 ). CTN has been proven to possess various biological activities, including antioxidant ( Guo et al, 2022 ), anti-tumor ( Dalil et al, 2022 ), antibacterial ( Zhong et al, 2021 ), and anti-inflammatory effects ( Wu et al, 2020 ). Li ( Popa et al, 2021 ) discovered that CTN effectively suppresses NSCLC cells invasion, proliferation and tumorigenesis.…”
Section: Natural Products Modulating Ferroptosis For Intervention In ...mentioning
confidence: 99%
“…Cryptotanshinone (CTN) is a diterpenoid monomer and a lipophilic component extracted from the dried roots and rhizomes of the traditional Chinese herb S. miltiorrhiza ( Li et al, 2021 ; Zhang et al, 2023 ). CTN has been proven to possess various biological activities, including antioxidant ( Guo et al, 2022 ), anti-tumor ( Dalil et al, 2022 ), antibacterial ( Zhong et al, 2021 ), and anti-inflammatory effects ( Wu et al, 2020 ). Li ( Popa et al, 2021 ) discovered that CTN effectively suppresses NSCLC cells invasion, proliferation and tumorigenesis.…”
Section: Natural Products Modulating Ferroptosis For Intervention In ...mentioning
confidence: 99%
“…233 Cryptotanshinone comes from natural medicines and has the advantages of low toxicity and wide indications. [233][234][235] Yan et al found that cryptotanshinone inhibits tumour growth by promoting ferroptosis in granulocytic myeloid-derived suppressor cells and TNBC cells through proteomics, single-cell transcriptome sequencing, ferroptosis phenotype detection, DARTS, microthermophoresis and molecular docking. 236…”
Section: Cryptotanshinonementioning
confidence: 99%
“…Cryptotanshinone is a monomer with various pharmacological activities extracted from Salvia miltiorrhiza, which has various effects such as anticancer, anti‐inflammatory, anti‐oxidation, anti‐diabetes and anti‐obesity 233 . Cryptotanshinone comes from natural medicines and has the advantages of low toxicity and wide indications 233–235 . Yan et al.…”
Section: Natural Compounds Targeting Ferroptosis In Breast Cancermentioning
confidence: 99%
“…[22][23][24] Cryptotanshinone (CTS), a bioactive ingredient extracted from herbal plant Salvia miltiorrhiza Bunge, possesses anti-tumor activity on breast cancer. [25] More attractively, CTS can significantly inhibit STAT3 activation via blocking STAT3 phosphorylation at Tyr705. [26,27] Recent study has also proved the potential of CTS in inhibiting the phosphorylation of STAT3.…”
Section: Introductionmentioning
confidence: 99%